Sustainability Learning in Organizations: The Role of Human Resource Development and Proposed Framework (Sains Humanika, 2021)
Learning through training and development programmes has been seen as an important vehicle to embed sustainability in organizations. This paper aims to conceptualize a model of sustainability learning in organizations and to understand the pivotal role that Human Resource Development plays in facilitating the learning process. It also explores relevant contextual factors that may influence the learning process engaged by employees in developing knowledge about sustainability. To fully understand the process of sustainability learning in organizations, this paper analyzes relevant theories on sustainability, Human Resource Development and learning theories. Results of the literature review will act as a basis to propose a framework which future researchers may refer to in studying sustainability learning in organizations. The proposed framework shall act as a point of departure to the development of holistic sustainability learning model through initiatives of Human Resource Development.Â Â
Keywords: Sustainability learning; human resource development; contextual factors